What is community-level environmental literacy, and how can we measure it? A report of a convening to conceptualize and operationalize CLEL. Issue 10 (6th September 2022) - Gibson, Lauren M.; Busch, K. C.; Stevenson, Kathryn T.; Cutts, Bethany B.; DeMattia, Elizabeth A.; Aguilar, Olivia M.; Ardoin, Nicole M.; Carrier, Sarah J.; Clark, Charlotte R.; Cooper, Caren B.; Feinstein, Noah Weeth; Goodwin, Jean; et al.
Abstract: Environmental education research often emphasizes the importance of community context, but conceptualization and measurement of environmental literacy has mostly occurred at the individual level, often focusing on individual behaviors. The environmental problems facing the world today require collective action—communities coming together to address large-scale problems. Accordingly, understanding and encouraging collective action requires a shift in focus from individual to community-level environmental literacy (CLEL). Despite its importance, CLEL has been left largely undefined and unmentioned in environmental education literature. To understand the field's current conceptualizations and measurement strategies around CLEL, the authors held a convening of 24 researchers to discuss the topic. Here, we report the findings of this convening and present a series of tensions that emerged in conceptualizing and measuring CLEL. We see this area of research as rich with opportunity for innovation and offer considerations for researchers engaging in this work.